Contribution of Some Managerial Accounting Techniques to Achieve Market Share Requirements / Applied researchin the Al-Muthanna Cement Company (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The research aims to achieve market share requirements and reach the targeted competitive price through the application of management accounting techniques represented by continuous improvement technique and target costing under an Activity Based Cost (ABC) system and Activity Based Management (ABM), In Muthanna Cement Company to reach the rationalization of the cost of the product and maintain the required quality and improve the profitability of the company.The problem of research has emerged in the inability of local firms to enter into effective competition with other companies operating in the same economic sector, Because of the high cost of its products, Which led to the sale of the product at prices below its cost, and the inability of companies to achieve profits and thus difficult to compete in the market with foreign products.The research was based on the hypothesis that the application of management accounting techniques represented by [continuous improvement technique and target costing and Activity Based Cost (ABC) system and Activity Based Management (ABM)] , Leading to rationalization of the cost of the productand reach the targeted competitive price to achieve market share requirements,and increase the profits of the company under normal working conditions and the available energy and Its ability to improve the quality of its products.The application of management accounting techniques has been an important advantage for companies, therefore it’s needed to be applied in an Iraqi company, so Muthanna Cement Company was selected.The research concluded that the company and local companies can apply these two techniques because of their potentials,The research recommendation was based on the fact that local companies have the potential to apply these techniques because of its advantages and benefits in achieving the objectives of these companies in rationalizing the costs of their products and increasing their performance level and access to market share through reaching competitive prices.